Eisenhower and Landrum-Griffin : A Study in Labor-Management Politics - Lee, R. Alton (Book collections on Project MUSE., 1990)
During the 1950s two Senate investigations, both highly publicized through the new medium of television, revealed the spread of racketeers and corruption among labor unions. Taking advantage of these sensational revelations, business interests, who for years had chafed against the federal government's pro-labor policies, mounted a campaign to curb labor's power. With the support of the business-oriented administration of Dwight Eisenhower, they pushed through Congress a new ""reform"" law -- the Landrum-Griffin Act. In this book, R. Alton Lee, author of an earlier study of the Taft-Hartley law.